Strategi Pengembangan Akreditasi Manajemen Penggunaan Obat Dengan Metode Hanlon Di IFRSUD Sultan Imanuddin Pangkalan Bun - Poppy Dwi Citra Jaluri; R.A. Oetari; Gunawan Pamudji Widodo (Jurnal Farmasi Indonesia, 2016)
To improve the quality of services and improve patient safety in providing hospital services needed hospital accreditation. The purpose of this study was to determine the level of conformity seven accreditation standards MMU based from KARS and strategy development pharmacy installation with Hanlon method. This study is a non-experimental research design in Hospital Pharmacy Installation Sultan Imanuddin Pangkalan Bun, Central Kalimantan, data collection conducted by using a questionnaire instrument to 28 respondents are Pharmacists and TTK. After the problem was found in each element and then analyzed using the Hanlon method. Research concluded that the level suitability to the accreditation standards of pharmacy service MMU is MMU1 85.36%, 92.39% MMU2, MMU3 78.75%, 88.57% MMU4, MMU5 50.24%, 72.32% MMU6, and MMU7 42.62% and development strategy appropriate priorities to be applied in IFRSUD Sultan Imanuddin Pangkalan Bun, Central Kalimantan are still does not meet the maximum standards.